Moderate Islamic Jurisprudence: Study of Muhammadiyah's Decision on Changes in Criteria for Fajr Prayer Time (UINSI Samarinda, 2021)
This article aims to look at the new criteria decided by Muhammadiyah regarding the beginning of Fajr prayer time, which was seen through the conception of religious moderation (wasatiyah) in Indonesia. This issue relates to the decision regarding the change in the criteria from -20 degrees to -18 degrees due to an 8-minute difference from the common schedule used in Indonesia. This decision resulted in a long process that started from public unrest, discussed in the 27th National Conference of Muhammadiyah. Still, it could not be realized, then Muhammadiyah conducted a comprehensive fiqh study and appointed 3 main institutions to conduct studies astronomically. After the XXXI National Conference on Tarjih, Muhammadiyah finally decided to change this criterion through the principle of wasaṭiyyah; there is nothing wrong with this ijtihad jama`i carried out by Muhammadiyah, but Muhammadiyah does not appear to be balanced and fair in using the research results of the institutions that have been appointed, besides that Muhammadiyah also does not consider other important research outside Muhammadiyah. In the context of wasaṭiyyah, these different principles need to be resolved. The solution to unification itself must be given to the country’s religious authorities. The government is also required to fix criteria and conceptions to maximize that union effort.